Analysis of the Impact of Smoking Behavior on Communities in Coastal Area, Indonesia: A Review - Indah Normayanti Sulaeman; Hasmawati (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Smoking behavior remains a significant public health concern with adverse effects on both individuals and the wider community. In coastal areas, smoking has become ingrained as part of the local lifestyle, contributing to various health risks. Objective: This study aims to analyze scientific articles related to the impact of smoking behavior among coastal communities in Indonesia. Methods: This research employed a Systematic Literature Review (SLR) approach. The review focused on journal articles published in Indonesian, sourced from Google Scholar and ResearchGate between 2014 and 2024. The search utilized keywords such as “smoking behavior of coastal communities.” The literature indicates that smoking is a common habit among individuals living in coastal areas. Results: The review identified several smoking-related health problems, including hypertension, acute respiratory infections (ARIs), elevated levels of low-density lipoprotein (LDL) cholesterol, and oral and dental health issues. However, some findings diverge from theoretical expectations, such as studies showing no significant association between smoking behavior and the incidence of cataracts or musculoskeletal complaints. Conclusion: Smoking behavior poses serious health risks and contributes to a decline in quality of life. Therefore, it is essential for coastal communities to increase awareness of the health consequences of smoking and adopt healthier lifestyle choices to improve overall well-being. Keywords: Coastal Communities, Smoking Behavior, Health Impacts, Lifestyle, Indonesia.